Classroom management strategies in building student character at a superior elementary school based on the wetland ecoregion in North Banjarmasin District - Suhaimi Suhaimi; Noorahim W.; Ni'mah Ni'mah (HAFECS PRESS, 2025)
Ineffective classroom management can hinder efforts to develop students’ character, particularly in high-performing public elementary schools (SDN Unggul) located in wetland areas such as North Banjarmasin District. The unique environmental characteristics of these regions require more adaptive and context-based classroom management strategies. This community service activity aimed to enhance teachers’ capacity through training on classroom management strategies that support character development. The methods employed included participatory training through material delivery, group discussions, case studies, and hands-on classroom practice. The results showed a significant improvement in teachers’ competencies. The average score for classroom management understanding increased from 65.2 to 85.6 (+20.4), the ability to implement character-building strategies rose from 58.4 to 82.8 (+24.4), and proactive attitudes toward innovation improved from 60.1 to 87.2 (+27.1). The impact on students was also clearly measurable. Character observations indicated improvements in discipline from 68% to 85% (+17), responsibility from 62% to 83% (+21), cooperation from 59% to 80% (+21), and independence from 55% to 77% (+22). These findings affirm that contextually designed classroom management strategy training can make a tangible and measurable contribution to improving teacher competence and student character in high-performing elementary schools located within wetland ecoregions. Abstrak. Permasalahan manajemen kelas yang kurang efektif dapat menghambat upaya pembentukan karakter siswa, terutama di Sekolah Dasar Negeri (SDN) Unggul yang berada di kawasan lahan basah seperti Kecamatan Banjarmasin Utara. Karakteristik lingkungan yang khas menuntut adanya strategi pengelolaan kelas yang lebih adaptif dan kontekstual. Kegiatan pengabdian ini bertujuan untuk meningkatkan kapasitas guru melalui pelatihan strategi manajemen kelas yang mendukung penguatan karakter siswa. Metode yang digunakan meliputi pelatihan partisipatif melalui penyampaian materi, diskusi kelompok, studi kasus, dan praktik langsung di kelas. Hasil kegiatan menunjukkan peningkatan kompetensi guru yang signifikan. Rata-rata pemahaman manajemen kelas meningkat dari 65,2 menjadi 85,6 (+20,4), kemampuan penerapan strategi karakter naik dari 58,4 menjadi 82,8 (+24,4), dan sikap proaktif terhadap inovasi meningkat dari 60,1 menjadi 87,2 (+27,1). Dampaknya terhadap siswa juga terukur secara jelas. Observasi karakter menunjukkan peningkatan pada indikator disiplin dari 68% menjadi 85% (+17), tanggung jawab dari 62% menjadi 83% (+21), kerja sama dari 59% menjadi 80% (+21), dan kemandirian dari 55% menjadi 77% (+22). Temuan ini menegaskan bahwa pelatihan strategi manajemen kelas yang dirancang secara kontekstual dapat memberikan kontribusi nyata dan terukur dalam meningkatkan kompetensi guru serta karakter siswa di sekolah dasar unggul yang berada di wilayah ekoregion lahan basah.